A WRITTEN GRAMMATICAL ERROR ANALYSIS OF SECOND YEAR STUDENTS OF ARABIC - Adila, Wildi (Arabi : Journal of Arabic Studies, 2019)
Errors could likely be an integral part of the learning-teaching process. Writing errors of Arabic, in particular, are considered fundamental since they can act as significant data to determine the level of language proficiency, identify possible difficulties in student's writing, and prepare further teaching aids and materials to meet students' needs and problems. The objective of the current study, therefore, aimed to reveal the common types of errors and their frequencies committed by the students at University of Darussalam Gontor. The subjects of this research were fifteen students that were in the second year of their studies. The instrument utilised tests to elicit the primary data. The findings showed that the most committed error was idafa construction, followed by tenses and agreement. These errors were due to several causes, namely interference of L1, intralingual, overgeneralisation, and ignorance of rule restrictions. To cope with such errors, it is suggested that global errors and individual's concerns must be taken into primary consideration by language teachers.